2021
DOI: 10.1136/bmjopen-2021-048948
|View full text |Cite
|
Sign up to set email alerts
|

Impact of severe SARS-CoV-2 infection on nutritional status and subjective functional loss in a prospective cohort of COVID-19 survivors

Abstract: The nutritional sequelae of COVID-19 have not been explored in a large cohort study.ObjectivesTo identify factors associated with the change in nutritional status between discharge and 30 days post-discharge (D30). Secondary objectives were to determine the prevalence of subjective functional loss and severe disability at D30 and their associated factors.MethodsCollected data included symptoms, nutritional status, self-evaluation of food intake, Performance Status (PS) Scale, Asthenia Scale, self-evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
2
14
0
2
Order By: Relevance
“…As reported previously [17], 13.2% of the patients hospitalized for a severe form of COVID-19 were still severely malnourished 30 days after hospital discharge (weight loss > 10% and/or BMI < 17). The highest predictive factors of persistent malnutrition were ICU stay and male sex.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…As reported previously [17], 13.2% of the patients hospitalized for a severe form of COVID-19 were still severely malnourished 30 days after hospital discharge (weight loss > 10% and/or BMI < 17). The highest predictive factors of persistent malnutrition were ICU stay and male sex.…”
Section: Resultssupporting
confidence: 68%
“…In view of the latter, we found it useful to use a selfevaluation muscle strength scale, asking the patient how he/she rated his/her muscle strength compared to before the disease. In a preliminary study, we found a concordance between the outcome of this subjective functional evaluation (Self Evaluation of Strength (SES)) and that of the grip test [17].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Participants in our study were, on average, over 3 months post-positive-COVID-19 infection and fell into the long-COVID category. However, most research to date looking at malnutrition or malnutrition risk post-COVID-19 infection has had a short follow-up time of one month or less [ 11 , 21 , 22 ]. A study by Bedock et al followed 91 patients hospitalized for COVID-19 infection during admission and 30 days post-discharge and found that 28.6% of patients were malnourished, based on the Global Leadership Initiative on Malnutrition (GLIM) criteria, 30 days after discharge [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Bedock et al followed 91 patients hospitalized for COVID-19 infection during admission and 30 days post-discharge and found that 28.6% of patients were malnourished, based on the Global Leadership Initiative on Malnutrition (GLIM) criteria, 30 days after discharge [ 21 ]. Similarly, another study of 288 patients hospitalized for COVID-19 found that 33.3% of patients were malnourished based on GLIM criteria at 30 days after discharge [ 22 ]. In contrast, Filippo et al used the Mini Nutritional Assessment (MNA) to assess for malnutrition and found that 54.7% of patients were at risk for malnutrition, but only 6.6% were malnourished when evaluated in an outpatient clinic at a median of 23 days post-discharge for COVID-19 infection [ 11 ].…”
Section: Discussionmentioning
confidence: 99%